Pengaruh Corporate Governance terhadap Kinerja Pasar Emiten yang terdaftar di Indeks Saham Syariah Indonesia - Rizkary Roslianti (Jurnal Bisnis dan Keuangan, 2020)
Corporate governance is one of the important aspects for the company. The application of proper corporate governance will affect the company’s value and amrket performance. This study aims to analyze the effect of corporate governance that represented by institutional ownership, independent commissioner and managerial ownership toward market performance that represented by Tobin’s Q. This study used a quantitative approach using secondary data (annual finance report)companies listed on Indeks Saham Syariah Indonesia years 2016- 2018. This study used a significance level of 5%. Based on the regression analysis results, it indicates that institutional ownership and managerial ownership do not have significant effect on Tobin’s Q. On the other hand, indpendent commissioner has significant effect to the Tobin’s Q. Simultaneously, institutional ownership, independent commissioner and managerial ownership have significant effect to Tobin’s Q.